Is the transition from primary to secondary school a risk factor for energy balance-related behaviours? A systematic review - Helga Emke; Coosje Dijkstra; Stef Kremers; Mai JM Chinapaw; Teatske Altenburg (Cambridge University Press, 2023)
Abstract Objective: The substantial changes in the physical and social environment during the transition from primary to secondary school may significantly impact adolescents' energy balance-related behaviours (i.e. dietary behaviour, sedentary behaviour, sleep behaviour and physical activity (PA)). This is the first review systematically summarising evidence on changes in four energy balance-related behaviours of adolescents across the school transition from primary to secondary school. Design: For this systematic review, the electronic databases Embase, PsycINFO and SPORTDiscus were searched for relevant studies from inception to August 2021. PubMed was searched for relevant studies from inception to September 2022. Inclusion criteria were: (i) longitudinal studies reporting; (ii) one or more energy balance-related behaviours; and (iii) across the school transition, that is, with measurement(s) during both primary and secondary school. Setting: Transition from primary to secondary school Participants: Adolescents across the transition from primary to secondary school. Results: Thirty-four studies were eligible. We found strong evidence for an increase in sedentary time, moderate evidence for a decrease in fruit and vegetable consumption, and inconclusive evidence for a change in total, light, and moderate-to-vigorous PA, active transport, screen time, unhealthy snack consumption, and sugar-sweetened beverages consumption among adolescents across the school transition. Conclusions: During the transition from primary to secondary school, sedentary time and fruit and vegetable consumption tend to change unfavourably. More high-quality, longitudinal research is needed specifically on changes in energy balance-related behaviour across the school transition, especially regarding sleep behaviour. (Prospero registration: CRD42018084799)